Fibrogenesis in nonalcoholic steatohepatitis. (April 2011) - De Minicis, Samuele; Svegliati-Baroni, Gianluca
Nonalcoholic steatohepatitis includes a wide spectrum of liver injury, ranging from simple inflammation to fibrosis and cirrhosis. Whereas simple steatosis has a benign clinical course, steatohepatitis is a recognized cause of progressive liver fibrosis and can develop, in some circumstances, into cirrhosis. The main cause of fibrogenesis is represented by the activation of myofibroblastic cells, which then start to produce matrix filaments. Matrix-producing cells, although mainly constituted of hepatic stellate cells, may have a different origin in the liver. This article will provide information on the sources of matrix-producing cells and the mechanisms involved in the development of fibrogenesis, with particular attention paid to the pathophysiological implications leading from steatohepatitis to fibrosis and cirrhosis.